KENYA’S STANDARD GAUGE RAILWAY PROJECT IN THE CONTEXT OF THEORY AND PRACTICE OF REGIONAL PLANNING - Juma, Leanard Otwori; Adol Gogo, Fredrick; Abdulkadr, Ahmed Abduletif; Lóránt, Dénes Dávid (Acta Carolus Robertus, 2020)
Despite most African countries having immense natural and human resources potential, the continent has mostly been lagging on matters of economic development. This scenario could primarily be attributed to weak intra-regional and inter-country trade given the poor connectivity, quality, and diversity in transportation services and infrastructure. In this regard, the governments of the greater East African Region representing Tanzania, Rwanda, Burundi, Uganda, South Sudan, Ethiopia and Kenya, therefore, mooted a coordinated vision to develop interlinked regional infrastructure in road and rail transport to allow smooth movement of goods and services.  This paper aimed to critically review the impact of the SGR development on Kenya in the context of regional planning and development. The methodology of the study was a critical review of existing literature and secondary data. Study findings indicated that the development of the (Standard Gauge Railway) SGR is in tandem with the development strategies of other East African Countries. Its development is incorporated in national spatial plans with the rail route targeting regions with viable populations and sustainable economic activities. Criticisms, however, revolve around the ballooning debt to finance infrastructural development and lack of prioritization f mega projects. In conclusion, despite the financial constraints, the SGR is viewed to significantly influence the socio-economic spheres while presenting challenges in the management of landscapes where it traverses in Kenya and the Region.
Keywords: transportation; Kenya; regional planning; standard gauge railway